2022
DOI: 10.1080/21645515.2022.2054602
|View full text |Cite
|
Sign up to set email alerts
|

Burden of vaccine-preventable diseases among at-risk adult populations in the US

Abstract: Life-course immunization holds significant benefit for population health by reducing the burden of vaccine-preventable diseases (VPD) through vaccinating individuals at different stages and circumstances in life. The study aimed to determine the epidemiologic, clinical, economic, and societal burden of VPDs among at-risk adult subpopulations in the United States. A systematic literature review was conducted for articles published between January 2010 and June 2020, which identified 72 publications. There was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The prevalence rates of HBV infection and anogenital warts at enrollment were 4.8% and 8.6%, respectively, which were significantly higher than those in the general population (2.9% for HBV infection and 0.7% for anogenital warts) [ 10 11 ]. Our finding of a high incidence and prevalence of VPDs in HIV-infected patients is consistent with those of previous studies that reported an increased risk of VPDs in this population [ 6 12 13 ]. Therefore, prophylactic immunization is crucial for HIV-infected patients to prevent morbidity and mortality due to VPDs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The prevalence rates of HBV infection and anogenital warts at enrollment were 4.8% and 8.6%, respectively, which were significantly higher than those in the general population (2.9% for HBV infection and 0.7% for anogenital warts) [ 10 11 ]. Our finding of a high incidence and prevalence of VPDs in HIV-infected patients is consistent with those of previous studies that reported an increased risk of VPDs in this population [ 6 12 13 ]. Therefore, prophylactic immunization is crucial for HIV-infected patients to prevent morbidity and mortality due to VPDs.…”
Section: Discussionsupporting
confidence: 93%
“…Vaccination against influenza, pneumococcus, hepatitis A virus (HAV), hepatitis B virus (HBV), and human papilloma virus (HPV) is recommended for individuals living with HIV [ 2 ]. Several studies have highlighted the importance of prophylactic immunization in HIV-infected patients [ 3 4 5 6 ]. However, despite the importance of immunization, there are no available data on vaccination rates and the factors influencing vaccine acceptance in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…VPDs in adults impose a substantial burden to patients and the healthcare system, especially in the absence of life-course immunization programs. 74 Several studies have shown that infectious diseases lead to higher average costs per episode in patients with IC conditions compared with the general population. 36 , 75 , 76 In a retrospective healthcare database study conducted in the US, invasive pneumococcal disease (IPD) led to costs of $58.5 million per 100,000 patient years in people at high risk, including individuals with IC conditions and HIV, which were 23.4-fold higher compared with the general population.…”
Section: Resultsmentioning
confidence: 99%
“…VPDs may cause severe complications in this setting due to the immune system impairment, malnutrition and oncological treatments [ 2 ]. They represent a serious economic burden with a delay in the treatment of the underlying cancer [ 3 ]. Despite this evidence, vaccination rates are inadequate: during the 2021–22 season, the receipt of seasonal influenza vaccine among the subjects over 64 years of age was 57.2% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%